Differences in Nutritional Status of Elderly Users and Non Users of Complete Dentures - Nadia, Rosa; Kusuma, Hapsari Sulistya; Bakhtiar, Dika Agung (Jurnal Medali, 2023)
Background: Dental and oral health problems due to tooth loss will have an impact on nutritional intake and nutritional status of the elderly.The elderly who do not replace missing teeth using dentures will decrease their chewing efficiency. One of the functions of dentures is to restore the function of mastication and speech. Objective: Knowing the difference in nutritional status of elderly users and non-denture users in terms of body mass index using a literature review. Method: Literature review Searching for articles using four Science Direct, Google Scholar, EBSCO, and PubMed database using relevant keywords and obtained 12 article results that match the research criteria. Results: Normal nutritional status is greater in elderly users of complete dentures compared to elderly who do not use complete dentures. based on measurements of body mass index, denture users and non-users have a significant difference. Conclusion: The use of complete dentures can affect nutritional status.